The Poverty Alleviation Role of the “Insurance+Futures” Pattern—Evidence from 10 Chinese Provinces - Jinhong Han (Risks)
This paper sorts out the poverty reduction mechanism of the “insurance+futures” pattern and uses actual data from the top 10 provinces in China with the highest underwriting value in the “insurance+futures” pattern since 2016 to test it by a panel data model. The results show that the “insurance+futures” pattern has a significant effect on reducing poverty. By replacing the proxy variable for the dependent variable and changing the samples for testing, the results remained significantly valid, demonstrating the robustness of the conclusion.